2021
DOI: 10.1007/s10554-021-02355-4
|View full text |Cite
|
Sign up to set email alerts
|

Functional recovery after percutaneous revascularization of coronary chronic total occlusions: insights from cardiac magnetic resonance tissue tracking

Abstract: To evaluate the effect of percutaneous coronary intervention (PCI) of coronary chronic total occlusions (CTOs) on left ventricular (LV) strain assessed using cardiac magnetic resonance (CMR) tissue tracking. In 150 patients with a CTO, longitudinal (LS), radial (RS) and circumferential shortening (CS) were determined using CMR tissue tracking before and 3 months after successful PCI. In patients with impaired LV strain at baseline, global LS (10.9 ± 2.4% vs 11.6 ± 2.8%; P = 0.006), CS (11.3 ± 2.9% vs 12.0 ± 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
2
2
3
Order By: Relevance
“…Additionally, they reported significant improvement of GCS and of TCS of CTO territory in 150 patients. They also showed a significant 3‐month post PCI improvement of GRS by MRI‐FT in five CTO patients with impaired pre‐PCI GRS 19 . This is not in agreement with the current study, which may be due to different follow‐up duration, sample size and more selective inclusion criteria.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…Additionally, they reported significant improvement of GCS and of TCS of CTO territory in 150 patients. They also showed a significant 3‐month post PCI improvement of GRS by MRI‐FT in five CTO patients with impaired pre‐PCI GRS 19 . This is not in agreement with the current study, which may be due to different follow‐up duration, sample size and more selective inclusion criteria.…”
Section: Discussioncontrasting
confidence: 77%
“…The significant improvement in LCX TLS, which was not shown in the current study, may be due to different post‐PCI follow‐up intervals and different population size 18 . A further study by Everaars et al showed that while there was no significant GLS improvement by MRI‐FT following PCI in 150 CTO patients, there was a significant improvement in GLS in the 51‐patient sub‐group with impaired pre‐PCI GLS 19 …”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…So in this month's Journal, we learned that another group of investigators have seemingly stumbled on their own Eureka moment, employing intramyocardial radio-frequency tissue tagging to investigate local cardiac strains following angioplasty in high-risk cases [12].…”
mentioning
confidence: 99%